(untitled) - Singh, Nitish (Oxford, 2005)
In The Culturally Customized Web Site, Nitish Singh and Arun Pereira focus on cultural aspects of international website design, honing in on three objectives: * First, to present a review and survey results on standardization/localization issues on the web * Second, to present a scientifically tested framework to design culturally adapted international websites, and provide marketers and web designers with practical web localization tools * Third, to show readers the power and effectiveness of culturally customized websites This is the first book to address the issue of website standardization, localization—or what the authors refer to as “cultural customization”. Little evidence has been accumulated to show whether international consumers prefer to browse and buy from standardized global websites or websites adapted to local cultures. The Culturally Customized Web Site provides insights into whether the web is a culturally neutral medium of communication or a medium impregnated with cultural values. Also presented is empirical evidence as to whether local consumers prefer standardized websites or websites adapted to their culture. Visit www.theculturallycustomizedwebsite.com * The first book to offer a scientifically developed and validated theoretical framework to culturally customize web sites * Offers practical guidelines to marketing professionals in the international marketplace and challenges the practice of a standardized approach to global e-marketing * Provides illustrative examples of the power of culture in influencing web browsing and online buying behavior
Keywords: Web sites,Electronic commerce.,Web sites; Design.,Thiết kế